Attitudes towards academic dishonesty: Russian and British students - Shliakov, I (2022)
Literature on academic dishonesty has been widespread, but it has been approaching the issue from either the standpoint of morality or convention and plagued by methodological shortcomings. Going beyond previous studies based on Social Domain Theory, a vignette experiment was created to include both students’ perceptions of moral (fairness) and conventional (acceptability) judgements using a one between (Culture) × two within (Stakes and Exposure) factors design, controlling for academic integrity involving students from British (N = 113) and Russian (N = 453) universities. The vignettes were carefully calibrated using cognitive interviews and back-translations to fit both contexts. New findings emerged. First, this study found that perceptions of academic dishonesty involve both moral (fairness) and conventional (acceptability) judgements. Second, these judgements were affected by cultural and, in some instances, contextual factors. Specifically, British students perceived cheating as unfair and unacceptable, while Russian students regarded cheating as unfair but somewhat acceptable. Third, contextual drivers, such as harm perceptions, affected Russian students’ judgements on the fairness and acceptability of academic misconduct, while British students’ judgements were immune to contextual differences. Thus, Russian students had less negative attitudes toward cheating if it did not harm other students, and they condemned whistle-blowing in such cases, referring to a whistle-blower as a “snitch”. Finally, higher academic integrity was associated with lower perceptions of fairness and acceptability. These findings underscore that students’ judgements of academic dishonesty are multifaceted and malleable, urging more nuanced and cross-cultural investigations. On the policy side, they also suggest universities should introduce honour codes and develop courses on academic ethics, which have the potential to decrease the level of academic dishonesty.